Padronização de técnica histoquímica de mensuração de lipídios da epiderme de cães e mensuração de lipídios da epiderme de cães atópicos antes e após reposição tópica de lipídios e ceramidas - Salvador, Marcela Cazagrande [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Canine atopic dermatitis is a multifactorial skin disease with genetic origin, that causes itching as the main symptom. One of the disease's main characteristics (and a major causative factor) is the impairment of the epidermal skin barrier. This is caused, primarily, by a deficiency in the quantity of lipids in the epidermis of atopic dogs. However, no standardized histochemical technique for the evaluation of epidermal lipids in dogs exists in the literature. The objectives of this study were firstly, to standardize the measurement of lipids of the epidermis of normal dogs using specific histochemical staining. Secondly, using this standardized staining technique, ascertain the amount of epidermal lipids in atopic patients before and after treatment with topical replacement of lipids and compare with measurements from healthy dogs. For standardization of staining, epidermal samples from 25 healthy animals were taken and subjected to hematoxylin and eosin, Sudan Red and Oil Red O staining. The samples were processed using visual semi-quantitative assessment and by the digital image analysis program. After standardization, we compared the quantity of lipids in the epidermal barrier of 15 atopic dogs and 30 healthy dogs. Samples were taken from neck and axillae in all participating animals to assess any differences in lipid content between body regions. The results showed that Sudan Red provides the most accurate measurement of skin barrier lipids when comparing the lipid layer of the epidermis of healthy dogs with atopic dogs. It was found that atopic dogs exhibit a reduced quantity of lipids in the epidermal barrier prior to treatment and show a significant increase after topical replacement of lipids. Comparisons between individuals within the atopic group of animals showed that lipids from the neck occurred in smaller quantities than the axillary region. These results show that topical replacement of lipids in dogs with ...

A dermatite atópica canina é uma dermatopatia de origem genética, cujo principal sintoma é o prurido. Uma de suas principais características é o comprometimento da barreira epidérmica cutânea, causado por deficiência na quantidade de lipídios na epiderme destes cães. Não obstante, na literatura consultada não há uma padronização de técnica de coloração histoquímica para avaliação destes lipídios epidérmicos em cães. Este trabalho objetivou padronizar uma técnica digital de mensuração de lipídios da epiderme de cães normais utilizando-se colorações histoquímicas específicas e, por meio da coloração padronizada, mensurar a quantidade de lipídios epidérmicos de cães atópicos antes e após o tratamento com reposição tópica de lipídios, além de comparar a quantidade de lipídios da epiderme de cães atópicos com a de cães saudáveis. Para a padronização da técnica de coloração histoquímica foram utilizados vinte e cinco animais saudáveis, sendo as amostras submetidas a três colorações: hematoxilina & eosina, Sudan Red e Oil Red O. Em seguida, as amostras passaram por avaliação entre patologistas e pelo programa de análise de imagem digital, confrontando as duas técnicas. Após padronização, comparou-se a quantidade de lipídios da barreira epidérmica entre 15 cães atópicos e 30 cães saudáveis, comparando a quantidade de lipídios da epiderme da região cervical com a região axilar. Os resultados mostraram concordância entre a avaliação dos patologistas e o programa de análise digital, que ambas as colorações se prestam a este fim, mas que Sudan Red é a coloração que melhor permite a mensuração dos lipídios da barreira epidérmica e, quando comparada a camada lipídica da epiderme de cães saudáveis e cães atópicos, nota-se que estes possuem uma quantidade lipídica reduzida e, após o tratamento com reposição tópica de lipídios, os cães atópicos apresentam ...
Standardization of histochemical technique for measurement of epidermal lipids of dogs and measurement of epidermal lipids of atopic dogs before and after topical replacement of lipid and ceramides
Keywords: Cão - Doenças; Dermatite atópica; Histoquimica; Pele - Inflamação; Lipídios - Medição; Lipids - Measurement